(untitled) (ACME, 2021)
The main purpose of this article is to present a critique of the Nietzschean reading of the evaluative status of Euripides’ poetry within the historical-genealogical process that the philosopher understands as constituting the decline of the Greek tragedy. The negative character – supposedly radicalizing, potentializing and consuming this hypothetical trajectory of decline – of Euripidian poetry will here be imputed to the very theoretical conditioning of the Nietzschean conception of the tragic. To do this, we will explore three fundamental guidelines: (1) the subordination of Nietzsche to a traditional interpretative line; (2) his tendentious disregard for the concrete content of the whole Euripidian work; (3) the unfounded identification between Socrates and Euripides.